Existing Obstacles of the Third Party Logistics (3PL) Market in Sri Lanka - Malkanthie, M.A.A.; Jayamanna, J.M.D.J.N. (My University, 2017)
With the globalization of businesses and consequent competitive pressures, all companies try to deliver customized products all over the world quickly and on time. This has placed a number of demands on the logistics systems. While today the world logistic industry is practicing up to 7PL, within a short span of time, Sri Lanka is still grappling with 3PL activities. Therefore, the intention of this research is to identify the challenges, barriers / factors hindering the growth of the 3PL market in Sri Lanka to facilitate the growth of the industry to meet world competition. According to the findings, customers are quite happy with their 3PL providers, but they are not very satisfied as well as any high trust to the 3PL providers. Costs, lack of control, lack of coordination, lack of cooperation are the main issues that respectively affect the growth of the 3PL market in Sri Lanka. Inadequate capabilities are also one of the problems. Lack of control and lack of coordination are significant factors that diminish the satisfaction of customers and lack of control is the only significant factor that diminishes the trust of customers. 2 Minimizing lead time between delivery, adoption of new technology, handling the order channels multiplied by the number of delivery options and handling overstocks due to online sales, and adoption of new technology are considered the future challenges in 3PL market in Sri Lanka. Key Words: logistics, 3PL, satisfaction, trust, hindering issues